The Roles of Ideological State Apparatus in Maintaining Hegemony in Charles Dicken’s Hard Times - Prasetya, Farid Adi (LANTERN (Journal on English Language, Culture and Literature), 2013)
One of literary works, a novel, may be reflects social phenomenon. The correlation between literary works and social phenomenon includes an analysis towards a novel entitled Hard Times by Charles Dickens, which covers a social phenomenon. The overall image of Hard Times is a society of industrial city namely Coketown, which has unequal economic condition. Through characters that appear in the novel, it can be analyzed, Hard Times reflects social clashes that are triggered by economic condition and social class differentiation. Through Marxism point of view, the characters of Hard Times reflects a society which is distinguished vertically into bourgeoisie and proletariat, according to their roles within the economic activity in Coketown. This vertical distinction leads an inclination of bourgeoisie to maintain their domination within the society. This novel highlights that bourgeoisie then looks the role of Ideological State Apparatus, which is very effective to control Coketown society. The bourgeoisie then take opportunity from that condition to maintain their domination. As the result, this novel indicates that proletariat's struggles to get a better economic condition will always be pushed and restricted by the bourgeoisie, which successfully make an approach to the ISA such as religion, school, or media. Keyword: society, bourgeoisie, proletariat, hegemony, Ideoogical State Apparatus, Repressive State Apparatus.